Penerapan Kahoot! Sebagai Media Evaluasi pada Pembelajaran Instalasi Penerangan Listrik - Khaira Ummah; Oriza Candra (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to determine the application of kahoot as a learning evaluation tool in the class XI TITL electric lighting installation subject at SMKN 5 Padang. Technological advances in the world of education are currently increasing rapidly so that the application of learning evaluation requires new innovations to improve the quality of education in an all-digital era. This study uses a quantitative method with a descriptive approach. The object of this research is Kahoot and the use of kahoot as a learning evaluation tool in the Electrical Lighting Installation subject. The subjects in this study were students of class XI TITL 1 SMKN 5 Padang. The research instrument used was in the form of evaluation questions on kahoot in objective and True-False forms as well as student response questionnaires. Based on the response questionnaire regarding the use of kahoot, a positive response was received from students and subject teachers. The average value of students in answering questions using kahoot is in the high category based on the data that has been obtained so that it can be concluded that the application of kahoot as a learning evaluation tool in the subject of electric lighting installation meets the criteria for a good evaluation tool, namely valid, practical, and interesting for used as a learning evaluation tool.